Black reconstruction in America 1860-1880 : an essai toward a history of the part which black folk played in the attempt to reconstruct democracy in America - Du Bois, William Edward Burghardt (New York : Atheneum, 1972)
Bibliotheek François Vercammen
Engels
Monografie